(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article presents a specialized pedagogical framework for Food Technology students, integrating Content and Language Integrated Learning (CLIL) with the Lexical Approach. The core objective is to move beyond isolated vocabulary lists toward lexical chunks specifically used in food science, such as processing techniques, safety protocols, and chemical reactions. The study details an exploration of a 4-skill exercise system: reading, listening, writing, and speaking that designed to improve both professional competence and linguistic fluency.